An Exploration of Praktika Application as Self-Learning Speaking for English Teachers - Chatarina Novita Setyorini; Senowarsito Senowarsito; Arso Setyaji (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This study aims to explore the features of Praktika application for teachers’ speaking skills and teachers’ perceptions of the feature of Praktika application. This research was conducted in September 2024. The research used descriptive qualitative method with observation, interview, and questionnaire as the instruments. The respondents English teachers. Data were gathered by observation, interview, and questionnaire. The researcher conducted the study in several stages, starting with selecting qualified participants and observing their prior knowledge of the application. Participants then practiced speaking English using the application, while data was collected through participants perceiving learning to speak English in the Pratika application as self-learning. Finally, the researcher analyzed the gathered data using existing methods. Findings indicate that the Praktika application effectively supports English teachers in improving their pronunciation, sentence structures, and confidence in speaking. Additionally, teachers expressed positive perceptions of the application, highlighting its role in increasing motivation, engagement, and technical usability. The results suggest that Praktika can be a valuable self-learning tool for teachers and a recommended resource for students.